ChemInform Abstract: Highly Mono‐Selective ortho‐Trifluoromethylation of Benzamides via 8‐Aminoquinoline Assisted Cu‐Promoted C—H Activations. Issue 38 (September 2016) - Hu, Liang; Chen, Xiang; Gui, Qingwen; Tan, Ze; Zhu, Gangguo
Abstract: A trifluoromethylation of benzamides with Togni reagent II provides the corresponding aromatic mono(trifluoromethyl) amides by using a quinolinylamino group as directing group.